Creole drama : theatre and society in antebellum New Orleans - Braun, Juliane (Writing the early Americas., 2019)
"This book shows how New Orleans's francophone population used the theatre to maintain their political, economic, and cultural sovereignty in the face of growing Anglo-American dominance"--